FROM LOCAL TO GLOBAL: INTEGRATION OF THE CAMBRIDGE CURRICULUM AND THE INDEPENDENT CURRICULUM AS A MODEL OF MODERATE AND TOLERANT ISLAMIC EDUCATION - Siti Choiriyah; Mohamad Zubad Nurul Yaqin; Nurul Atikoh; Imelda Berliana Julyechia Sari (FORPIM PTKIS ZONA TAPAL KUDA, 2026)
The globalization of education presents both challenges and opportunities for Islamic schools in Indonesia. One response is the integration of the globally oriented Cambridge Curriculum with the nationally designed Merdeka Curriculum. This study explores such integration at SDI Islamic International School PSM Grogol Kediri, showing how local wisdom can meet global standards to promote moderate and tolerant Islamic education. Using a qualitative case study, data were collected through interviews, classroom observations, and analysis of curriculum documents and lesson plans. Findings indicate that integration is carried out through mapping the core content of Cambridge and Merdeka, collaborative lesson planning, and competency-based assessments that combine cognitive, affective, and character aspects. This practice improves learning quality, fosters critical thinking, and cultivates tolerance among students. The study confirms that merging local and global curricula can provide a model of Islamic education that nurtures love, inclusiveness, and social harmony.